Analysis of Drug Information Inquires at a Mental Hospital in Saudi Arabia - Alomi, Yousef Ahmed; Qahtani, Nada Al; Alsulami, Nora; Mashouf Al Qahtani, Mohamed; Almansor, Fahad Abdallah (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the analysis of drug information inquiries at a Mental hospital in Saudi Arabia. Method: It is 4.5- years cohort analysis of drug Information centers inquiries at a 500-bed Mental hospital in Riyadh city, Saudi Arabia. All drug information centers should enter the electronic answer form of drug information inquiries. American Society of Health-System Pharmacist (ASHP) drug information model. The form consisted of questioner demographic information, questioner contact information, patient demographic data, patient diagnoses or health problems, question classification, the specific inquiry, and answer, drop list of references (Tertiary resources, secondary resources, and primary resources), and pharmacist answered demographic data. The form made through survey monkey system. The format analyzed through the Microsoft Excel sheet version 10th. Results: The total of drug information inquiries was (1088). Most of the inquiries asked by pharmacist 504 (46.32%), physician 496 (45.59%) and patients 49 (4.5%). The most type of inquiries was drug dose 272 (25%), and drug of choice 204 (16.74%), followed by drug interaction 186 (17.1%) and adverse drug reaction 172 (15.81%). The physician frequently asked about adverse drug reaction 120 (24.19%) followed by drug dosing 106 (21.37%)and drug of choice 101 (20.36%). While the pharmacist most frequently asked about drug dosing 156 (30.95%) followed by drug interaction 100 (19.84%) and drug of choice 85 (16.87%). The most type of references used to answer the question was other 416 (38.52%) and Drug.com website 263 (24.35%) followed by Medscape website 226 (20.35%) and prescribing guidelines in psychiatry book 162 (15%). Conclusion: The drug information services prove comprehensive answering of drug inquiries at a mental hospital in Riyadh city, Saudi Arabia. The drug information services need update references and more awareness to medical staff.
Keywords: Drug information; Inquires; Mental hospital; Ministry of Health; Saudi Arabia